Scientific highlights of the 9th ESWI Influenza Conference - Leslie Reperant; Colin A. Russell; Albert Osterhaus (BMC, 2024)
Abstract The European Scientific Working Group on Influenza (ESWI) held the 9th ESWI Influenza Conference in Valencia from 17-20 September 2023. Here we provide a summary of twelve key presentations, covering major topics on influenza virus, respiratory syncytial virus (RSV) and SARS coronavirus 2 (SARS-CoV-2) including: infection processes beyond acute respiratory disease, long COVID, vaccines against influenza and RSV, the implications of the potential extinction of influenza B virus Yamagata lineage, and the threats posed by zoonotic highly pathogenic avian influenza viruses.